The Phenomenon of Covid-19 and Its Treatment in The Prophetic Sunnah Perspectives | ظاهرة الكوفيد: وقايتها وعلاجها في ظل المنهج النبوي - Bintu Syaifa Al-Azizah; Muhammad Khoirul Mustaghfirin (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2020)
This article examines the pandemic in the Prophet's tradition perspective, especially His method in managing, treating, and preventing the spread of a pandemic which can be applied today. This study uses library research to identify and locate relevant information on hadiths related to pandemics, epidemics, and quarantine from primary sources. The Hadiths, then, are extracted and authenticated from their collections (getting takhrij process) to reveal the judgment on practising, knowing the meaning of words as well as the explanations.